2019
DOI: 10.1038/s41598-019-44164-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of stannous fluoride and amine fluoride containing oral hygiene products: A 4-year randomized controlled pilot study

Abstract: This 4-year randomized controlled trial (RCT) aimed at investigating whether routine home use of both a SnCl 2 /AmF/NaF-containing mouth rinse and toothpaste has a preventive effect on oral health. Fifty-four test subjects were examined in biannual intervals. The primary endpoint “dental erosion” was determined by the Basic Erosive Wear Examination (BEWE). The secondary endpoints were “saliva pH”, “dentin hypersensitivity” generated by Visual Analogue Scale (VAS), and “discoloration” mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This result was also confirmed by the clinical data on the oral health status demonstrated by the biannual caries assessment by the ICDAS-II-System for both groups 33 . The clinical data on erosion showed that the treatment group yielded a better result after four years with less increment in erosion 34 . In this respect the continual use of these products as a preventive measure for tooth erosion can be recommended for patients with a high risk of erosion and can be considered as contributing to oral health in general.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This result was also confirmed by the clinical data on the oral health status demonstrated by the biannual caries assessment by the ICDAS-II-System for both groups 33 . The clinical data on erosion showed that the treatment group yielded a better result after four years with less increment in erosion 34 . In this respect the continual use of these products as a preventive measure for tooth erosion can be recommended for patients with a high risk of erosion and can be considered as contributing to oral health in general.…”
Section: Discussionmentioning
confidence: 89%
“…The study was registered at the German Clinical Trials Registry Platform (DRKS00005019, registration 2013/05/27). Previous studies have shown that endurance athletes are at a higher risk of erosive tooth wear than controls 34 . For this reason, 54 participants who performed at least five hours of endurance training per week were recruited between March and October 2013 and included in the study.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In high concentrations, it also forms deposits on the tooth surface, creating an Sn-rich layer, which has been shown to be more acid-resistant than pure CaF 2 [Schlueter et al, 2009a]. Unfortunately, the use of stannous ions might be associated with some drawbacks, as tooth or tongue discoloration and astringent feeling on the mucosa [Addy, 2008;Frese et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…So far, polyvalent fluoridated com-pounds, such as stannous fluoride (SnF 2 ) or the combination of fluoride with a stannous salt (commonly SnCl 2 ), have shown encouraging results [Ganss et al, 2008;Schlueter et al, 2009b]. However, stannous-containing formulations have been associated with some drawbacks, such as tooth staining and unpleasant taste [Frese et al, 2019].…”
Section: Introductionmentioning
confidence: 99%